Implementing One-at-a-Time Therapy in community addiction and mental health centres: a retrospective exploration of the implementation process and initial outcomes - Laura M. Harris-Lane; Natalie R. Keeler-Villa; Alexa Bol; Katie Burke; AnnMarie Churchill; Peter Cornish; Sarah F. Fitzgerald; Bernard Goguen; Kristina Gordon; Alexia Jaouich; Rino Lang; Mylène Michaud; et al. (BMC, 2023)
Abstract Background The Department of Health of the Government of New Brunswick and Regional Health Authorities elected to implement Stepped Care 2.0 (SC2.0) in 2021, and began with One-at-a-Time (OAAT) therapy in Community Addiction and Mental Health Centres (CAMHCs) to facilitate rapid access to addiction and mental healthcare. This study: 1) explicated the process of implementing OAAT therapy as it aligned to evidence-based implementation frameworks and strategies; 2) assessed readiness for change among providers during the implementation; and 3) evaluated initial client and system outcomes. Methods The process of implementing OAAT therapy within CAMHCs was documented and retrospectively aligned with the Active Implementation Frameworks-Stages of Implementation, Consolidated Framework for Implementation Research, and incorporated strategies endorsed by the Expert Recommendations for Implementing Change. Providers working in CAMHCs completed online asynchronous courses in OAAT therapy and SC2.0, and were recruited to participate in research on perceptions of organizational readiness. Initial outcomes of the implementation were evaluated through client satisfaction surveys administered in CAMHCs and system performance indicators. Results Aligning with implementation stages, key strategies included: 1) continuously monitoring readiness and soliciting stakeholder feedback for iterative improvement; 2) building a representative implementation team with engaged leaders; 3) creating a comprehensive implementation plan on staff training, communication, and system changes; and 4) supporting sustainability. Providers who participated in research (N = 170, ~ 50% response rate) agreed that their organization was ready for implementation, and that OAAT therapy delivered within a SC2.0 framework was acceptable, appropriate, and feasible. More than 3,600 OAAT therapy sessions were delivered during the initial implementation stage, and waitlists were reduced by 64.1%. The majority of clients who completed surveys (N = 1240, ~ 35% response rate) reported that their OAAT therapy session was helpful, with a minority reporting that additional intervention was needed. Conclusions Thoughtful planning and execution, aligned with evidence-based implementation frameworks and strategies, played an important role in this provincial change initiative. Implementation steps outlined can help inform others looking to enact large-scale change.